A journey of ta’awun (cooperative behaviour) in edu-action at IIUM Mkitchen® and Masjid al-Syakirin Gombak (MASG) - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Mhd. Sarif, Suhaimi; Ahmad H.Osman, Rahmah; Man, Saupi; Jaapar, Ghazali; Abdul Razak, Dzuljastri; Mohamadali, Noor Azizah; Abdul Aziz, Normaziah; Mohamad Ali, Noor Azian; Mahri, Nurhafizah; et al. (Meso Publishing, 2021)
This book narrates the journey of ta’awun (cooperative behaviour) at IIUM Mkitchen® project with Masjid Al-Syakirin Gombak (MASG). The main objective of the project is transform the mosque as a platform to provide free food, to up skill in foodpreneurship, to create new employment opportunities, to give empowerment and to nurture entrepreneurship (3Es) for poor and needy people in the surrounding area of it. Ta’awun refers to cooperative behaviour among the participants, the sponsors, and the beneficiaries in initiating, planning, sponsoring, executing and evaluating the Mkitchen® project at Masjid Al-Syakirin Gombak (MASG). The journey officially started on 24th January 2021 through its first meeting among the interested as well as committed members. After executing two events, the project was continued with a full scale project for a month. The project has secured its proof of concept (POC). Nevertheless, the project has been continued with a small scale due to the movement restriction by the authority to prevent the spread of coronavirus disease (COVID-19).